Purification of Human Interferon Alpha-2b from Eschericha Coli Using Aqueous Two-Phase Systems - Lin, Yu Kiat (2011)
Interferon-alpha2b (IFN-α2b) has very high market value since it can be used in treating many diseases. Nevertheless, the development of an efficient and cost-effective purification process has been referred as the important part of IFN production since the biopharmaceutical product cost relies much on the purification process. Aqueous two-phase systems (ATPSs) require simply low investment cost and capable to integrate the numerous conventional downstream processes into a single step. Thus, this experimental project focused on the design of different ATPSs to reduce the steps in purification, thereby increasing the yield and reducing the cost and time of production. Purification of intracellular human recombinant IFN-α2b from Escherichia coli (E. coli) using polyethylene glycol (PEG)/potassium phosphate ATPS was investigated. The influences of system parameters including PEG molecular weight, tie-line length (TLL), volume ratio (VR), biomass loading, pH system and sodium chloride (NaCl) concentration (%w/w) were studied. The results showed that the optimum condition for purification of IFN-α2b was achieved at 4.0% (w/w) PEG-8000, 13.0% (w/w) potassium phosphate, 0.5% (w/w) NaCl, VR of 0.2, pH 6.5 and 10% (w/w) crude load. A purification factor (PFT) of 26.3 and 40.7% recovery yield were achieved in the optimized process. Furthermore, an alcohol/salt-based ATPS for the purification of intracellular human recombinant IFN-α2b was studied. The influences of 9 biphasic systems comprising alcohol-based top phase (ethanol, 2-propanol and 1-propanol) and salt-based bottom phase (ammonium sulfate, potassium phosphate and sodium citrate) were investigated in IFN purification. The results showed that the optimum condition for purification of IFN-α2b was achieved in ATPS of 2-propanol 18% (w/w) with ammonium sulfate 22% (w/w) system in the presence of 1.0% (w/w) NaCl. The purified IFN-α2b recorded a PFT of 16.24 with the yield of 74.64%. The effectiveness of ATPS for the purification of IFN-α2b was proven in this study. These ATPS purification methods provided alternative methods for IFN-α2b purification. The PFT result of PEG/ potassium phosphate ATPS is higher than the PFT result recorded in alcohol/salts ATPS. Therefore, suggesting that the PEG/ potassium phosphate ATPS is the prominent method for IFN-α2b purification.